2013
DOI: 10.3390/ijms140612827
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Arachis hypogaea AREB1 Gene Enhances Drought Tolerance by Modulating ROS Scavenging and Maintaining Endogenous ABA Content

Abstract: AhAREB1 (Arachis hypogaea Abscisic-acid Response Element Binding Protein 1) is a member of the basic domain leucine zipper (bZIP)-type transcription factor in peanut. Previously, we found that expression of AhAREB1 was specifically induced by abscisic acid (ABA), dehydration and drought. To understand the drought defense mechanism regulated by AhAREB1, transgenic Arabidopsis overexpressing AhAREB1 was conducted in wild-type (WT), and a complementation experiment was employed to ABA non-sensitivity mutant abi5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 50 publications
2
53
0
Order By: Relevance
“…Higher GST transcript levels in RAV1xABI5 under imposed drought and a high level in all transgenics during stress recovery (Figure ) suggest the ‘less‐stressed’ phenotype is due to combating stress through increased levels of ROS scavengers. Similar results were recently reported for Arabidopsis expressing a peanut ABI5 homologue (Li et al ., ). Reduced AdhA transcript in transgenics (and synergistic reductions in RAV1xABI5) under WW, drought and recovery conditions (Figure ) supports the hypothesis of a less‐stressed phenotype for ABI5 and RAV overexpressing cotton.…”
Section: Discussionmentioning
confidence: 97%
“…Higher GST transcript levels in RAV1xABI5 under imposed drought and a high level in all transgenics during stress recovery (Figure ) suggest the ‘less‐stressed’ phenotype is due to combating stress through increased levels of ROS scavengers. Similar results were recently reported for Arabidopsis expressing a peanut ABI5 homologue (Li et al ., ). Reduced AdhA transcript in transgenics (and synergistic reductions in RAV1xABI5) under WW, drought and recovery conditions (Figure ) supports the hypothesis of a less‐stressed phenotype for ABI5 and RAV overexpressing cotton.…”
Section: Discussionmentioning
confidence: 97%
“…Our results are consistent with the conclusion that AhAREB1 is the key negative regulator of AhNCED1 expression, while AhNAC2 is simply an enhancer of this inhibitory effect. Furthermore, both AhNAC2 and AhAREB1 can improve the drought tolerance of the plant by inducing stress-related gene expression2728, meaning that both TFs are activators of the ABA signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work on peanut ( Arachis hypogaea ), an important cash crop, we cloned and identified NCED1 ( AhNCED1 ), NAC2 ( AhNAC2 ) and AREB1 ( AhAREB1 )42526. Furthermore, we showed that both AhNAC2 and AhAREB1 are induced by ABA in peanut, and that, in an Arabidopsis AhAREB1 -overexpression line, transcription of AtNCED3 is significantly suppressed2728. The AhNCED1 promoter was also cloned, and bioinformatics analysis showed that it contained one NACRE and four ABRE core sequence elements29.…”
mentioning
confidence: 92%
“…A c c e p t e d M a n u s c r i p t 8 Accumulation of ROS in the leaves of stress treated plants was examined based on the histochemical staining with nitro-blue-tetrazolium (NBT) following the method of Li et al (2013). For this purpose, the control and salt treated WT and transgenic leaves were stained under dark with NBT (0.1 mg/mL) for 36 h at 25°C.…”
Section: Page 8 Of 33mentioning
confidence: 99%